The Efficacy of Ginsenoside Rg3 Combined with First-line Chemotherapy in the Treatment of Advanced Non-Small Cell Lung Cancer in China: A Systematic Review and Meta-Analysis of Randomized Clinical Trials - Peng, Ze; Wu, Wen Wen; Yi, Ping (Frontiers in Pharmacology, 2021)
Background: For advanced non-small cell lung cancer (NSCLC) patients, first-line chemotherapy is the main treatment in the clinic despite its efficacy is limited and adverse effects are always inescapable. Ginsenoside Rg3 has been increasingly wide used as an adjuvant in first-line chemotherapy for advanced NSCLC patients in China, while no comprehensive meta-analyses have been conducted to estimate the efficacy and safety of ginsenoside Rg3 combined with first-line chemotherapy on advanced NSCLC. Methods: Randomized controlled trails using a combination of first-line chemotherapy and ginsenoside Rg3 for advanced NSCLC patients were searched and selected from six databases. The Cochrane Risk of Bias tool was used to assessed the quality of these selected original researches. And we used Review Manager 5.3 and STATA to analyze the data. Results: Twenty-two studies with 2202 patients were included in our review. The results showed that compared with first-line chemotherapy alone, the combination of ginsenoside Rg3 and first-line chemotherapy could improve the objective response rate (ORR) (RR [95% CI], 1.44 [1.27, 1.63], P<0.00001 ), the disease control rate (DCR) (RR [95% CI], 1.24 [1.12, 1.38], P<0.0001), KPS (RR [95% CI], 1.62 [1.42, 1.84], P <0.00001), one-year survival rate (RR [95% CI], 1.49 [1.08, 2.06], P=0.01), two-year survival rate (RR [95% CI], 6.22 [1.68, 22.95], P=0.006), weight (RR [95% CI], 1.31 [1.04, 1.66], P=0.02), and reduce the VEGF level (RR [95% CI], -2.21 [-4.03, -0.38], P=0.02), the incidence of gastrointestinal reactions(RR [95% CI], 0.66 [0.47, 0.93], P=0.02) and bone marrow suppression (RR [95% CI], 0.43 [0.30, 0.61], P<0.00001). Conclusions: These analyses showed that a treatment combination of first-line chemotherapy and ginsenoside Rg3 could improve the objective response rate, the disease control rate and patient's quality of life, as well as reduce side effects, which provided a new strategy to optimal the treatment of advanced NSCLC.